SOME CONSIDERATIONS ON THE HISTORIOGRAPHY OF RIVER CROSSINGS IN THE PERIOD OF AMIR TEMUR AND THE TEMURIDS - Mo‘ydinov D. A. (TARIXIY TADQIQOTLAR, 2026)
This article presents some considerations on the historiography of river waterways and river crossings in the period of Amir Temur and the Temurids. The river crossings of the Temurid period and their impact on political, socio-economiclife are analyzed on the basis of historical analysis and new scientific conclusions are presented. Brief information is provided on the activities of scientists who have studied the history of river crossings of the Temurid period to date.